Surface wave inversion and detection of underground objects - Aung Aung Myo Win (2014)
Laboratory experiments, numerical modelling and field surface wave tests were performed in this research in relation to seismic surface wave methods. From laboratory experiments, multimodal surface wave propagation encountered in pavement systems and soil medium with underground objects were studied. Rayleigh surface wave propagation in semi-infinite domain was studied through finite element (FE) modelling. Selection of appropriate domain size for modelling a semi-infinite domain using non-reflecting boundary conditions (NRBCs) was discussed. Field surface wave tests were conducted at residual soil sites and pavement sites. Newly proposed Weighted Average Velocity (WAVe) inversion algorithm was applied to determine the shear wave velocity profiles of these test sites. Finally, active and passive surface wave measurements were conducted to detect culvert drains located below layered soil media and a pavement system. Finite element (FE) modelling was also performed to complement field test data.